Analysis of ability to listen to descriptive text through the implementation of the learning team’s strategy student - Paath, Ruth C (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The purpose to be achieved in this study is that students could have the ability to analyze and gather to descriptive text through the application of the listening team strategy, especially 2nd semester students in class A majoring in Indonesian Language and Literature Education in the 2019/2020 academic year. The research method used is descriptive qualitative method according to its type. The subject of this research is the ability to listen to descriptive texts of 2nd semester students in the 2019/2020 academic year majoring in Indonesian Language and Literature Education. The source of data is class A 2nd semester students totaling 32 people and lecturers of Listening Skills courses. To collect data, the technique used is a combined triangulation of observation and tests. The data analysis technique is inductive based on the facts obtained in the learning process and then constructed according to its type. The process goes through several stages starting with orienting the learning process, all data is described, the next stage is reduction or focus on the problems that arise during learning then selected according to the type, the last stage is analyzed. The results of the study state that the learning teams learning strategy has had a positive impact on student responsibility and activity in analyzing the description text that has been listened to during learning. Of the thirty-two students participating in the learning, 25 students have carried out their responsibilities 'well', 5 people are classified as quite good, and 2 people are 'not good'. The test results showed that 27 students answered correctly and 5 students still needed further guidance. The application of the learning teams strategy can improve the ability to analyze descriptive texts from listening to second semester students of the Department of Indonesian Language and Literature Education FBS Unima because the achievement is maximum.